DOI: 10.33915/etd.3608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Gonadotropin Mixture on Reproductive Success in Progesterone- Treated Non-Lactating Anestrous Ewes

Abstract: Using exogenous gonadotropins as part of an estrous induction protocol can have beneficial effects on fertility in ewes bred out-of-season. Few studies have evaluated the efficacy of P.G. 600®, a mixture of gonadotropins with FSH-like and LH-like activity, to increase fertility in anestrous ewes and, in particular, following pre-treatment with progesterone delivered via controlled internal drug releasing (CIDR) devices. The objective of this study was to evaluate the effects of P.G. 600® on reproductive succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 93 publications
(175 reference statements)
1
1
0
Order By: Relevance
“…Our findings promote interpretative statement that, the high preovulatory level of circulating estrogen is responsible for induces estrous behavior (Moakhar et al, 2012), and consequently promotes higher levels of estrogen production by the growing follicles, that improve the occurrence of estrus (Dogan and Nur, 2006). So, one would expect estrous responses to be positively correlated with estrogen concentration during the peri-estrus period (Mondal et al, 2006) as a sequel of gonadotropin doses (D'Souza, 2013). Moreover, current observation reinforce the hypothesis of Yildiz et al (2004) they suggests that the prolonged estrus probably results in elevation of circulating estrogen that causes LH peak.…”
Section: This Interpretation Enhanced Bysupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings promote interpretative statement that, the high preovulatory level of circulating estrogen is responsible for induces estrous behavior (Moakhar et al, 2012), and consequently promotes higher levels of estrogen production by the growing follicles, that improve the occurrence of estrus (Dogan and Nur, 2006). So, one would expect estrous responses to be positively correlated with estrogen concentration during the peri-estrus period (Mondal et al, 2006) as a sequel of gonadotropin doses (D'Souza, 2013). Moreover, current observation reinforce the hypothesis of Yildiz et al (2004) they suggests that the prolonged estrus probably results in elevation of circulating estrogen that causes LH peak.…”
Section: This Interpretation Enhanced Bysupporting
confidence: 77%
“…Similarly, Barrett et al (2004) and Habibizad et al (2015) found that the mean serum estradiol concentrations for the pre-and early post-ovulatory periods were higher in eCG treated ewes compared to the control group. Moreover, the higher doses of gonadotropin (400-600 IU/eCG) would presumably lead to more estrogen production (Moakhar et al, 2012 andD'Souza, 2013) from the largest follicle which is the principal source of estradiol (Munoz-Gutierrez et al, 2002).…”
Section: This Interpretation Enhanced Bymentioning
confidence: 99%